TOURIST SATISFACTION WITH GASTRONOMIC TOUR PACKAGES IN BAKAS TOURISM VILLAGE - Wijanarko, Nikolas Mert; Febianti, Febianti; Arcana, Komang Trisna Pratiwi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This research is the first to evaluate tourist satisfaction with the Bakas Village gastronomic tour package, which is based on applied science in the field of economics. The research aims to explore how gastronomic tourism, which is the experience of local food and culture, can attract and satisfy tourists in Bakas Village, a rural area in Bali, Indonesia. Observation, interviews, documentation, and distributing questionnaires were used as data collection methods in this research. Qualitative and quantitative descriptive data analysis with a Likert scale was used as a data analysis method. In this research, it is known that gastronomic tourism meets this definition. Apart from that, tourists are also treated to other activities that are not listed in the tour packages sold, such as cooking classes, cultural performances, and farm visits. This research also shows that tourists who buy gastronomic packages from Bakas Village are satisfied with what they get. The novelty of this research is that it introduces a new concept of gastronomic tourism in Bakas Village, which is different from the conventional tourism in Bali that focuses on the natural and cultural attractions. The research also provides empirical evidence of the high level of tourist satisfaction with the gastronomic tour package, as measured by the indicators of service quality, food quality, and cultural authenticity. The research contributes to the literature on tourism and economics by highlighting the role of gastronomic tourism in enhancing the economic and social development of Bakas Village.